Determinants of stunting reduction in Ethiopia 2000 – 2011. Issue 2 (10th May 2016) - Woodruff, Bradley A.; Wirth, James P.; Bailes, Adam; Matji, Joan; Timmer, Arnold; Rohner, Fabian
Abstract: The prevalence of stunting in Ethiopia declined from 57% in 2000 to 44% in 2011, yet the factors producing this change are not fully understood. Data on 23, 999 children 0–59 months of age from three Demographic and Health Surveys (DHS) from 2000, 2005, and 2011 were analyzed to assess the trends in stunting prevalence, mean height‐for‐age z‐scores (HAZ) and the associations between potential factors and HAZ. Associations were determined separately using three separate generalized linear models for children age less than 6 months, 6–23 months, and 24–59 months of age. Significant variables were then analyzed to determine if they showed an overall trend between the 2000 and 2011 surveys. In children < 6 months of age, only mother's height was both a significant predictor of HAZ and showed a progressive, albeit non‐significant, increase from 2000 to 2011. In children 6–23 months of age, only mother's use of modern contraception showed substantial changes in a direction consistent with improving HAZ, but improvements in maternal nutrition status were observed from 2000 to 2005. For children 24–59 months of age a consistent and progressive change is seen in child's diarrhea, fever, mother's education, and the occurrence of open defecation. Our analysis demonstrated that factors associated with HAZ vary by child's age and the dominant livelihood practice in the community. Variables that could have contributed to the decline of stunting in Ethiopia in children less than 5 years of age include markers of child health, mother's nutritional status, mother's educational level, and environmental hygiene.